Quantifying cancer: Metrics, self-sustainable philanthropy, and tacit epistemological ethics in an East Indian cancer hospital - Robert D. Smith (Taylor & Francis Group, 2023)
This article ethnographically traces the performance of data collection and analysis for a cancer cost-of-illness study in an East Indian Cancer hospital. By reflecting on my experience in this project, I show how the hospital's obligations for philanthropic and business self-sustainability spatially and temporally structured data in a way that produced the conditions of possibility for what was able to be made knowable of patients' experiences in cancer health economics. While collecting and analysing data within the spatial and temporal structuring of this self-sustainable hospital, I argue that our research team attempted to craft an ethical epistemology by incorporating the unique realities of Indian cancer patients based upon assumptions made from our tacit knowledge. Specifically, we called upon this knowledge to exercise a form of tacit epistemological ethics for patients existing in an in-between space of classification within Euro-North America cancer health economics frameworks. Finally, I suggest that in light of an attempt to produce a more ethical economic logic, the results of the cost-of-illness analysis are ultimately returned to larger conditions of possibility within austere health systems and Euro-North America health economics frameworks.